Character and Temperament Dimensions in Subjects with Depressive Disorder: Impact of the Affective State on Their Expression - Bajraktarov, Stojan; Novotni, A; Arsova, Slavica; Gudeva Nikovska, Danche; Vujovikj, Viktorija (Scientific Foundation SPIROSKI, 2017)
The depression is a cross-cultural condition that occurs in all cultures and within all nations with certain specificities, even though there are some differences in its manifestation. The hereditary load is of major importance, but also the individual personality factors, in the form of risk factors, are associated with the occurrence of depression. Personality characteristics have a significant impact on the occurrence of the recurrent depressive disorder and the outcome of the treatment as well.